Gender differences in presentation and management of behavioral and psychological symptoms associated with dementia among nursing home residents with moderate to severe dementia. (2nd November 2021) - Resnick, Barbara; Galik, Elizabeth; Kolanowski, Ann; VanHaitsma, Kimberly; Boltz, Marie; Zhu, Shijun; Ellis, Jeanette; Behrens, Liza; Eshraghi, Karen
ABSTRACT: Lack of identification and management of behavioral and psychological symptoms of dementia (BPSD) can negatively impact female residents. The purpose of this secondary data analysis was to explore gender differences in presentation and management of BPSD and quality of interactions between residents and staff. A total of 553 residents from 55 nursing homes were included. Males exhibited more apathy and sexually inappropriate behavior and females exhibited more anxiety and sadness. Anxiety and sexually inappropriate behavior were more likely to be addressed in care plans for males than females. There was no difference in how staff interacted with males or females.